Assessment of Risk Factors for Non-Alcoholic Fatty Liver Disease (NAFLD): Assessment of Risk Factors for NAFLD - Hussain, Zahid; Rind, Muhammad Aslam; Nazir, Maria; Saleem, Muhammad (Pakistan Journal of Health Sciences, 2023)
The most frequent cause of chronic liver disease globally is non-alcoholic fatty liver disease (NAFLD). Potential risk factors for NAFLD have not received enough attention in Pakistan even though NAFLD has received substantial research. Objective: To assess risk factors for Non-alcoholic fatty liver disease. This study was conducted at the Department of Medicine Liaquat University, Hospital Jamshoro from 7th September 2020 to 6th March 2021. Methods: This research was cross-sectional. The study recruited a total of 195 patients via nonprobability sequential sampling. The ultrasound of all the patients was done by a sonologist for detecting NAFLD. Results: The stratification of NAFLD according to smoking, hypertension, obesity, hyperlipidaemia, uncontrolled diabetes mellitus, vitamin D deficiency was done. The statistical significance was observed for NAFLD in accordance with smoking, (p=0.00), hypertension (p=0.04), obesity (p=0.04), hyperlipidaemia (p=0.03), uncontrolled diabetes mellitus (p=0.04), vitamin D deficiency (p=0.04). Conclusions: This study has shown that the percentage of NAFLD was highest in age group (40-49 years). Males were more affected as compared to females. Smokers, hypertensives, hyperlipidemics and diabetics were more prone to develop NAFLD.